2022
DOI: 10.46876/ja.1126331
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organic Mulch Materials on Weed Control in Cucumber (Cucumis sativus L.) Cultivation

Abstract: This study was carried out in Iğdır University Şehit Bülent Yurtseven Campus to investigate the effects of different mulch materials on weed control, cucumber yield and soil temperature and moisture in cucumber (Cucumis Sativus L.) cultivation in 2020 and 2021. Five mulch materials (flax cover, peat, chopped paper, straw and fresh grass) were used in the study. Temperature and humidity loggers were used in the study. The research was established in a randomized block design with 7 characters and 4 replications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Mulching can contribute to a reduction in weed development, which can consequently reduce the labour required for weeding. This finding corroborates previous studies that highlighted the weed control benefits of mulching in crop production [14,45,46].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mulching can contribute to a reduction in weed development, which can consequently reduce the labour required for weeding. This finding corroborates previous studies that highlighted the weed control benefits of mulching in crop production [14,45,46].…”
Section: Discussionsupporting
confidence: 93%
“…Such studies have shown how the adoption of agroecological practices (use of mulch, organic manures, biochar, cover crops, livestock manure, etc.) can improve the nutritional quality and shelf life of crops, soil health, biodiversity and the sustainability of agricultural land [4,7,11,[13][14][15]. Although agroecology has been shown globally to address environmental and social issues [11,15], its monetary impact has not been sufficiently demonstrated in low-income countries in West Africa.…”
Section: Introductionmentioning
confidence: 99%